DNA Polymerase β as a Novel Target for Chemotherapeutic Intervention of Colorectal Cancer - Jaiswal, Aruna S.; Banerjee, Sanjeev; Aneja, Ritu; Sarkar, Fazlul H.; Ostrov, David A.; Narayan, Satya (PLOS ONE, 2011)
Chemoprevention presents a major strategy for the medical management of colorectal cancer. Most drugs used for colorectal cancer therapy induce DNA-alkylation damage, which is primarily repaired by the base excision repair (BER) pathway. Thus, blockade of BER pathway is an attractive option to inhibit the spread of colorectal cancer. Using an in silico approach, we performed a structure-based screen by docking small-molecules onto DNA polymerase β (Pol-β) and identified a potent anti-Pol-β compound, NSC-124854. Our goal was to examine whether NSC-124854 could enhance the therapeutic efficacy of DNA-alkylating agent, Temozolomide (TMZ), by blocking BER. First, we determined the specificity of NSC-124854 for Pol-β by examining in vitro activities of APE1, Fen1, DNA ligase I, and Pol-β-directed single nucleotide (SN)- and long-patch (LP)-BER. Second, we investigated the effect of NSC-124854 on the efficacy of TMZ to inhibit the growth of mismatch repair (MMR)-deficient and MMR-proficient colon cancer cell lines using in vitro clonogenic assays. Third, we explored the effect of NSC-124854 on TMZ-induced in vivo tumor growth inhibition of MMR-deficient and MMR-proficient colonic xenografts implanted in female homozygous SCID mice. Our data showed that NSC-124854 has high specificity to Pol-β and blocked Pol-β-directed SN- and LP-BER activities in in vitro reconstituted system. Furthermore, NSC-124854 effectively induced the sensitivity of TMZ to MMR-deficient and MMR-proficient colon cancer cells both in vitro cell culture and in vivo xenograft models. Our findings suggest a potential novel strategy for the development of highly specific structure-based inhibitor for the prevention of colonic tumor progression.